Metamorfoses do cinema brasileiro na era da mundialização neoliberal: em busca de uma identidade estética? - Jorge Nóvoa (Araucaria)
This essay intends to define from a conceptual argument related to underdevelopment, growth, underdeveloped movies, movies of the colonized and of the conqueror, the historical phases of the evolution of the Brazilian movies, arriving to the present phase, of the neoliberal globalization of the national economies, and, consequently, of the Brazilian one. I maintain the idea that, today more than never, the dichotomy between the inside and the outside of the national economy does not find more sustentation and that with the globalization process, the hegemonic movies had incorporated the movies of the colonized. The result is a much big resemblance between world cinemas in what concerns to the utilization of special effects and high technology. None of the national cinemas, including the Brazilian movies, succeeds in the foundation of true news esthetics schools. This is the sign of the present era.